Threats to Democracy : the Radical Right in Italy after the War. - Ferraresi, Franco (Princeton University Press, 2001)
This book represents the first systematic research by a social scientist on the radical right-wing movements in Italy since 1945. During the heyday of right-wing violence between 1969 and 1980, street aggressions, attacks, and murders were commonplace. These bloody episodes were assumed to be the work of fanatical bands of "political soldiers" and urban warriors loosely controlled by secret services and other covert groups, which used them as part of a "strategy of tension" pursued in domestic and international circles. Franco Ferraresi here acknowledges that these rightist groups were in fact.